Incidence, mortality and survival in multiple myeloma compared to other hematopoietic neoplasms in Sweden up to year 2016 - Hemminki, Kari; Försti, Asta; Hansson, Markus (Scientific reports, 2021)
Survival in multiple myeloma (MM) has developed favorably over the past decades for reasons that have been ascribed to new medications and treatment. However, development of survival over a long period and comparison to other hematopoietic neoplasms (HN) is less well known. Here we used Swedish cancer data from the Nordcan database, spanning a 50-year period from 1967 to 2016, and analyzed 1- and 5-year survival data. As a novel type of analysis we calculate the difference in survival between year 1 and 5 which indicates how well survival was maintained in the 4-year period following year 1 after diagnosis. The relative 1- and 5- year survival increased constantly; the 5-year survival graph for women was almost linear. The difference between 1- and 5-year survival revealed that the 5-year survival gain was entirely due to the improvement in 1-year survival, except for the last period. Survival improvement in all HNs exceeded that in MM. The linear 5-year survival increase for female MM patients suggests a contribution by many small improvements in the first year care rather than single major events. The future challenges are to push the gains past year 1 and to extend them to old patients.
Keywords: Švédsko; Female; Mortality; ženské pohlaví; Registries; lidé; mnohočetný myelom; databáze faktografické; míra přežití; mortalita; Incidence; Male; Sweden; hematologické nádory; incidence; Aged; Hematologic Neoplasms; Survival Rate; Databases, Factual; lidé středního věku; registrace; Multiple Myeloma; senioři; mužské pohlaví; Middle Aged; Humans